Guilt in the body and brain : a psychophysiological and neuroimaging investigation - Fourie, Melike Marethe (Department of Psychology, 2014)
Guilt has been described as a quintessential moral emotion with an important regulatory function for the individual and society. Few studies have, however, empirically investigated guilt, largely because of challenges associated with its real-time elicitation. I aimed to elucidate the physiological and neural correlates of guilt by developing two novel emotion elicitation paradigms.